1986
DOI: 10.1128/iai.52.1.151-155.1986
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of killing of Toxoplasma gondii by rat peritoneal macrophages

Abstract: Rats are resistant to Toxoplasma infection, and macrophages are thought to mediate this resistance. We performed a series of experiments to investigate the mechanism of the anti-Toxoplasma activity of resident rat peritoneal macrophages. Resident rat peritoneal macrophages killed more than 90% of ingested Toxoplasma gondii in vitro.This capacity was reduced progressively with the prolongation of culturing of macrophages in vitro before challenge with T. gondii. Exhaustion of the respiratory burst of macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In contrast, serum‐opsonized C. albicans is normally ingested and killed by macrophages derived from cord blood, although these cells have a reduced capacity to respond to interferon‐γ (IFN‐γ) 38 . Furthermore, antimicrobial activity was similar in peritoneal macrophages from neonatal and adult mice, 39 and rats 40 , 41 . Apparently, the mechanisms of phagocytosis and killing in macrophages in the lungs are less mature when compared to macrophages from other sites in the first weeks after birth.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, serum‐opsonized C. albicans is normally ingested and killed by macrophages derived from cord blood, although these cells have a reduced capacity to respond to interferon‐γ (IFN‐γ) 38 . Furthermore, antimicrobial activity was similar in peritoneal macrophages from neonatal and adult mice, 39 and rats 40 , 41 . Apparently, the mechanisms of phagocytosis and killing in macrophages in the lungs are less mature when compared to macrophages from other sites in the first weeks after birth.…”
Section: Discussionmentioning
confidence: 90%
“…In vitro experiments have demonstrated that mouse peritoneal macrophages permit proliferation of Toxoplasma tachyzoites, but rat peritoneal macrophages, human alveolar and peritoneal macrophages, and human monocytes do not (Jones & Hirsch, 1972;Wilson & Remington, 1979;McLeod et al 1983;Chincilla, Portilla & Guerrero, 1986;McCabe & Remington, 1986;Catterall et al 1987). However, little information is available about the interaction between Toxoplasma and neutrophils which are the first inflammatory cells to infiltrate any site of infection.…”
Section: Introductionmentioning
confidence: 99%
“…These species are highly susceptible to T. gondii, and their resident macrophages are unable to kill the organism. In contrast, resident alveolar and peritoneal macrophages from rats are capable of killing large numbers of T. gondii (4,20), and we recently postulated that this might account for the remarkable resistance of rats to Toxoplasma infection (4,15,33). The results of the present study are consistent with that view, since human subjects are also relatively resistant to T. gondii and their macrophages also kill this parasite.…”
Section: Discussionmentioning
confidence: 99%